Optimalisasi Pemberdayaan Perempuan Melalui Literasi Hukum Tentang Pernikahan Tidak Tercatat dan Hak Nafkah Berbasis Participatory Action Research - Nadiyah, Nadiyah; Nazmi, Nahdia (JPM: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve the legal literacy of marginalized women in Pagatan Besar Village through education and mentoring regarding unregistered marriages and the right to maintenance using the Participatory Action Research (PAR) method. A total of 23 participants, the majority of whom were women of productive age, participated in the entire series of activities, which included training, simulations, group discussions, and pre-post evaluations to measure the level of legal understanding before and after the activity. The results of the implementation showed a significant increase in participant understanding, where more than 90% understood the concept and definition of unregistered marriage, the legal and social consequences it brings, and the rights to maintenance attached to wives and children. In addition, ? 90% of participants showed increased legal awareness, practical skills in identifying and resolving family law problems, and confidence in demanding their rights through legal channels. Participants also gave positive responses to the material, interactive delivery methods, and the mentoring approach that was contextual to their social realities. However, this activity has limitations, such as the coverage area, which only covers one village, the relatively short duration of the intervention, and the unmeasured long-term administrative impact. Thus, this service concludes that PAR-based legal literacy is effective in increasing legal awareness and empowerment of marginalized women and is recommended for replication on a wider scale.